Proposição de sistema de aproveitamento de água de chuva para o Campus Campina Grande do IFPB: estudo da viabilidade econômica - Marques., Célia Medeiros (2012)
The expectation of drinking water shortage for the next years has been a motivating factor to search for alternatives to supply the demand of future generations, to promote rational use of water and to reduce its waste. Once water is directly linked to people s maintenance and quality of life, also jeopardizing all living species in our planet, it is imperative that the entire civil, business and industrial society as well the government and its public institutions seek mechanism to preserve it. This research aimed at proposing a system of rainwater usage for Campina Grande campus of the Federal Institute of Education, Science and Technology of Paraíba IFPB and analyzing the economic viability of its establishment. The general goal was to evaluate the possibility of rainwater usage for non-drinking use in flush toilets, car wash and garden watering as sustainable mechanism of water rational usage in order to minimize drinking water waste, reduce costs of water bought by the institution and to comply with the sustainability criteria required by the Normative Instruction number 01/2010 of the Planning, Budget and Management Ministry MPOG. The methodological approach was based on descriptive and exploratory parameters, with data obtained in loco by means of photographic and documental registers of the mentioned IFPB campus. In order to develop this study, data was collected referring to supply of rainwater in the region, and the survey of annual water consumption in the cited campus, the estimate of non-drinking water demand and the measurement of the storage reservoir were accomplished. Economic analysis of the investment was done by financial mathematical tools, and for a 787 m3 reservoir, the cost involved of R$ 180.447,44, the benefit/cost ratio of 2,52, the payback period of 9,83 years and the net present value of R$ 274.701,45 were found. Therefore, the economic viability of the rainwater harvesting system implementation was proved and it showed to be attractive, especially when it requires a very high demand of water with less noble purposes, as it is the case. The proposed system allowed the storage of rainwater which meets a demand of 94% of non-drinking consumption of the mentioned campus. This will provide meaningful saving of water acquired from the Water Company of Paraíba CAGEPA.